Potencialidades das terras para uso agrícola de biossólidos de esgotamento sanitário na região intermediária Santa Maria - RS - Cunha, Henrique Noguez da (2023)
The sewage treatment process generates a residual sludge that can be transformed into a safe and usable product, called biosolids, through neutralization and sanitation processes. These biosolids can be used as fertilizer and soil enhancer. This study aimed to identify the potential areas for the use of sewage sludge biosolids in the Santa Maria intermediate region Rio Grande do Sul/Brazil. The analysis was based on data from soil, geomorphology, depth of the groundwater table, proximity to urban areas and roads, and permanent preservation areas, and it was performed in accordance with the CONAMA 375/06 resolution. Furthermore, the study evaluated the soil's suitability for the reception of biosolids. These results were interpreted to highlight priority land use areas in the Santa Maria-RS intermediate region. The Santa Maria intermediate region was divided into four subregions, and the results were reported for each subregion and the intermediate region as a whole. The intermediate region showed that 42% of its area could be used superficially without incorporation, 49% could be used superficially with incorporation, 51% could be used subsurfacely and in furrows, and 52% could be applied within pits. The soil suitability analysis in legally allowed areas showed that most of the area was restricted, with both suitable and unsuitable areas. The two most prominent agrosilvopastoral classes in the intermediate region were agriculture and livestock farming, and they were considered as priority use classes, regardless of soil suitability for biosolid use.